Refractory Plasmonic Metal Nitride Nanoparticles for Broadband Near‐Infrared Optical Switches. Issue 6 (2nd May 2019) - Xian, Yuehui; Cai, Yu; Sun, Xiaoyu; Liu, Xiaofeng; Guo, Qiangbing; Zhang, Zuxing; Tong, Limin; Qiu, Jianrong
Abstract: Ultrafast laser‐induced thermalization‐cooling of carriers in plasmonic nanostructures has been extensively explored in the development of high‐speed photonic switches with a broad operating bandwidth. However, potential laser damage arising from the strong light–matter interaction remains a tremendous obstacle for practical applications of most colloidal processed plasmonic nanoparticles (NPs). Here, it is demonstrated that titanium nitride (TiN) NPs, with a broadband localized surface plasmon resonance in the near infrared (NIR) region, can be exploited as an ultrafast optical switch based on transient photo‐bleaching, which manifests as a saturable absorption behavior with strong optical nonlinearity. The developed TiN‐based optical switches exhibit high robustness against laser damage (up to peak power of 557 GW cm −2 ) and enable both Q‐switched and transform‐limited mode‐locked pulse generation in the NIR spectral region in either fiber or solid‐state lasers with pulse duration down to 763 fs. The results may stimulate further exploration of metal nitride materials for applications in nonlinear optics and ultrafast photonic devices. Abstract : Potential damage arising from the strong light–matter interaction remains a tremendous obstacle for the practical applications of low‐dimensional saturable absorbers. Inside the surface plasmon resonance region, refractory titanium nitride nanoparticles with predominant stability are used as optical switches in producing short pulsed lasers.